String Processing and Information Retrieval 15th International Symposium, SPIRE 2008, Melbourne, Australia, November 10-12, 2008. Proceedings - Amir, Amihood; Turpin, Andrew; Moffat, Alistair (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed proceedings of the 15th International Symposium on String Processing and Information Retrieval, SPIRE 2008, held in Melbourne, Australia, in November 2008. The 25 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 54 submissions. The papers are organized in topical sections on compression and performance, information retrieval scoring and ranking, string matching techniques, self-indexing, string matching: space and practicality, information retrieval, non-standard matching, and bioinformatics.